2013
DOI: 10.1016/j.jfineco.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Why does junior put all his eggs in one basket? A potential rational explanation for holding concentrated portfolios

Abstract: Empirical studies of household portfolios show that young households, with little financial wealth, hold underdiversified portfolios that are concentrated in a small number of assets, a fact often attributed to behavioral biases. We present a potential rational alternative: we show that investors with little financial wealth, who receive labor income, rationally limit the number of assets they invest in when faced with financial constraints such as margin requirements and restrictions on borrowing. We provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…A number of papers have shown how standard deviations of equity portfolios can be reduced by diversification and how many randomly selected stocks are needed to eliminate idiosyncratic risks, starting with the by now famous Evans and Archer's () article, and followed by Benjelloun (), Bloomfield, Leftwich, and Long (), Campbell, Lettau, Malkiel, and Xu (), Domian, Louton, and Racine (), Elton and Gruber (), Statman (, ), and others. Suggested explanations for the underdiversification puzzle include preferences for lottery stocks (Barberis & Huang, ), margin and borrowing restrictions (Roche, Tompaidis, & Yang, ), solvency constraints (Liu, ), financial literacy (von Gaudecker, ), and other channels. But how large are the aggregate costs retail investors suffer from underdiversification?…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers have shown how standard deviations of equity portfolios can be reduced by diversification and how many randomly selected stocks are needed to eliminate idiosyncratic risks, starting with the by now famous Evans and Archer's () article, and followed by Benjelloun (), Bloomfield, Leftwich, and Long (), Campbell, Lettau, Malkiel, and Xu (), Domian, Louton, and Racine (), Elton and Gruber (), Statman (, ), and others. Suggested explanations for the underdiversification puzzle include preferences for lottery stocks (Barberis & Huang, ), margin and borrowing restrictions (Roche, Tompaidis, & Yang, ), solvency constraints (Liu, ), financial literacy (von Gaudecker, ), and other channels. But how large are the aggregate costs retail investors suffer from underdiversification?…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical studies which analysed household portfolios found different investors' behaviors compared to the theoretical suggestions, even if they do not arrive at a single explanation. Some of them find that diversification increases with either investor wealth or income (Kelly, 1995;Polkovnichenko, 2005;Goetzmann & Kumar, 2008), but other factors affecting investors behaviours could be age, financial sophistication, size of the account balance, portfolio size, labour income, and the ratio of current wealth to income (Calvet, Campbell, & Sodini, 2007;Ivković, Sialm, & Weisbenner, 2008;Goetzmann & Kumar 2008;Kumar, 2009;Roche, Tompaidis, & Yang, 2013).…”
Section: The Exchange Traded Funds Asset Classmentioning
confidence: 99%
“…Results from prior research showed that income and wealth were related to portfolio allocation (Anderson, 2013;Goetzmann & Kumar, 2008;Roche, Tompaidis, & Yang, 2013) and portfolio performance (Calvet, Campbell, & Sodini, 2006). For example, Anderson (2013) discovered a positive relationship between the proportion of stocks allocated in risky assets and the level of household wealth and income.…”
Section: Economic Situationsmentioning
confidence: 99%